2017
DOI: 10.1080/10916466.2017.1370476
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal oxide nanoparticles as surfaces for surface-assisted laser desorption/ionization mass spectrometry of asphaltenes

Abstract: We report the first use of NiO, Fe3O4, TiO2, and Co3O4 nanoparticles as surfaces for surface-assisted laser desorption/ionization (SALDI) mass spectrometry of asphaltenes. Higher signal-to-noise ratios (S/Ns) for asphaltene species were observed using NiO and Fe3O4 nanoparticles for SALDI as compared to LDI, where both surfaces consistently provided 2- to 3-fold improved S/Ns. The new SALDI detection method showed reliable adsorption data measuring supernatant solutions after 24 hour asphaltene adsorption on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…77 Moreover, the acidic nature of the zeolite beta BEA-NPs were also found effective in adsorbing asphaltenes from a toluene solution. 80 Synthesized maghemite (γ-Fe 2 O 3 ) NPs also showed higher 83 Similar results were reported for SiO 2 NPs, which showed higher adsorption affinity toward asphaltenes than MgO and Al 2 O 3 because of larger surface areas (adsorption efficiency was in the order of SiO 2 > MgO > Al 2 O 3 84 ). The smallest mean particle size and high surface area were also responsible for strong adsorption of asphaltenes from a Heptol solution onto the modified acidic SiO 2 NPs.…”
Section: Metal Oxidessupporting
confidence: 73%
See 2 more Smart Citations
“…77 Moreover, the acidic nature of the zeolite beta BEA-NPs were also found effective in adsorbing asphaltenes from a toluene solution. 80 Synthesized maghemite (γ-Fe 2 O 3 ) NPs also showed higher 83 Similar results were reported for SiO 2 NPs, which showed higher adsorption affinity toward asphaltenes than MgO and Al 2 O 3 because of larger surface areas (adsorption efficiency was in the order of SiO 2 > MgO > Al 2 O 3 84 ). The smallest mean particle size and high surface area were also responsible for strong adsorption of asphaltenes from a Heptol solution onto the modified acidic SiO 2 NPs.…”
Section: Metal Oxidessupporting
confidence: 73%
“…Variations in the adsorption affinities, capacities, and kinetics of the metal oxide NPs are attributed to the surface area and abundance of active sites available for adsorption. ,,− It was demonstrated that NiO NPs exhibit greater adsorption affinity than Fe 3 O 4 and Co 3 O 4 NPs. This was attributed to larger surface areas of the NiO NPs compared to Fe 3 O 4 and Co 3 O 4 NPs .…”
Section: Asphaltene Adsorption Onto Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…A home-built TOF mass spectrometer operated in the linear mode and equipped with a 50-Hz pulsed nitrogen laser; 337 nm (~3.68 eV) (model VSL-337ND, Laser Science Inc., Franklin, MA) was used to obtain the SALDI-TOF mass spectra presented herein. 47 All acquired mass spectra were a sum of 50 single laser shots. The voltages on the ion source acceleration lenses were set to 20 kV and 17 kV.…”
Section: Methodsmentioning
confidence: 99%